Short term outcomes of prostate biopsy in men tested for cancer by prostate specific antigen: prospective evaluation within ProtecT study. - Rosario, D; Lane, J; Metcalfe, C; Donovan, J; Doble, A; Goodwin, L; Davis, M; Catto, J; Avery, K; Neal, D; Hamdy, F (2012)
OBJECTIVES: To measure the effect of the adverse events within 35 days of transrectal ultrasound guided biopsy from the perspective of asymptomatic men having prostate specific antigen (PSA) testing; to assess early attitude to re-biopsy; to estimate healthcare resource use associated with adverse events due to biopsy; and to develop a classification scheme for reporting adverse events after prostate biopsy. DESIGN: Prospective cohort study (Prostate Biopsy Effects: ProBE) nested within Prostate Testing for Cancer and Treatment (ProtecT) study. Participants Between 1999 and 2008, 227,000 community dwelling men aged 50-69 years were identified at 352 practices and invited to counselling about PSA testing. 111,148 attended a nurse led clinic in the community, and 10,297 with PSA concentrations of 3-20 ng/mL were offered biopsy within ProtecT. Between February 2006 and May 2008, 1147/1753 (65%) eligible men (mean age 62.1 years, mean PSA 5.4 ng/mL) having 10 core transrectal ultrasound guided biopsy under antibiotic cover in the context of ProtecT were recruited to the ProBE study. OUTCOME MEASURES: Purpose designed questionnaire administered at biopsy and 7 and 35 days after the procedure to measure frequency and effect of symptoms related to pain, infection, and bleeding; patients' attitude to repeat biopsy assessed immediately after biopsy and 7 days later; participants' healthcare resource use within 35 days of biopsy evaluated by questionnaire, telephone follow-up, and medical note review; each man's adverse event profile graded according to symptoms and healthcare use. RESULTS: Pain was reported by 429/984 (43.6%), fever by 172/985 (17.5%), haematuria by 642/976 (65.8%), haematochezia by 356/967 (36.8%), and haemoejaculate by 605/653 (92.6%) men during the 35 days after biopsy. Fewer men rated these symptoms as a major/moderate problem-71/977 (7.3%) for pain, 54/981 (5.5%) for fever, 59/958 (6.2%) for haematuria, 24/951 (2.5%) for haematochezia, and 172/646 (26.6%) for haemoejaculate. Immediately after biopsy, 124/1142 (10.9%, 95% confidence interval 9.2 to 12.8) men reported that they would consider further biopsy a major or moderate problem: seven days after biopsy, this proportion had increased to 213/1085 (19.6%, 17.4% to 22.1%). A negative attitude to repeat biopsy was associated with unfavourable experience after the first biopsy, particularly pain at biopsy (odds ratio 8.2, P<0.001) and symptoms related to infection (7.9, P<0.001) and bleeding (4.2, P<0.001); differences were evident between centres (P<0.001). 119/1147 (10.4%, 8.7% to 12.3%) men reported consultation with a healthcare professional (usually their general practitioner), most commonly for infective symptoms. Complete data for all index symptoms at all time points were available in 851 participants. Symptoms and healthcare use could be used to grade these men as follows: grade 0 (no symptoms/contact) 18 (2.1%, 1.3% to 3.3%); grade 1 (minor problem/no contact) 550 (64.6%, 61.4% to 67.8%); grade 2 (moderate/major problem or contact) 271 (31.8%, 28.8% to 35.1%); grade 3 (hospital admission) 12 (1.4%, 0.8% to 2.4%); and grade 4 (death) 0. Grade of adverse event was associated with an unfavourable attitude to repeat biopsy (Kendall's τ-b ordinal by ordinal 0.29, P<0.001). CONCLUSION: This study with a high response rate of 89% at 35 days in men undergoing biopsy in the context of a randomised controlled trial has shown that although prostate biopsy is well tolerated by most men, it is associated with significant symptoms in a minority and affects attitudes to repeat biopsy and primary care resource use. These findings will inform men who seek PSA testing for detection of prostate cancer and assist their physicians during counselling about the potential risks and effect of biopsy. Variability in the adverse event profile between centres suggests that patients' outcomes could be improved and healthcare use reduced with more effective administration of local anaesthetic and antibiotics. Trial registration Current Controlled Trials ISRCTN20141297.